Witnessing in the age of the database: Viral memorials, affective publics, and the assemblage of mourning. (October 2016) - Papailias, Penelope
Many terms, such as spontaneous shrines, grassroots memorials and performative commemoratives, have been used to describe the collaborative on-site and online memorials created following the deaths of national and global figures, as well as those of unknown victims of mass-mediated disasters. I argue that the adjective "viral" better captures the temporality, spatiality, materiality, and mimeticism of these formations, as well as their frequent pathologization. Contemporary performative public mourning follows from mediated witnessing in the era of networked digital media, forming a witnessing/mourning assemblage. The corporeal testifying of the witness-turned-mourner contributes material derivatives to an affective network. Breaking from constative, narrative testimony and the exclusionary logic of the monument, these memorial aggregations emerge from processes of database (de)composition and network virality. Through the close analysis of a 2008 YouTube memorial video tribute for victims of a Greek bus accident, I consider shifts in public grieving and memorialization of catastrophic media events in relation to developments in web protocols and platforms.